2021
DOI: 10.51791/njap.v32i2.1094
|View full text |Cite
|
Sign up to set email alerts
|

Influence of irrigation intervals on dry matter yield, concentration of crude protein, calcium and phosphorus in Lablab purpureus and Sorghum almum fodder in the sudan savanna zone of Nigeria

Abstract: Irrigation trials were conducted in the late dry season (March to June) with Lublab (Lablab purpureus) and Columbus grass (Sorghum almum) in the Sudan savanna of Nigeria. The objective of this study was to determine the dry matter yield (IDM/ha), crude protein (CP), calcium (Ca) and phosphorus(P) in dual-purpose lablab bean and Sorghum almum at 3 irrigation schedules (5, 7 and 10 days irrigation interval). The results obtained showed dry matter yield in lablab increased (P<0.05) and varied from 1.7 to 11.7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
2
1
2
Order By: Relevance
“…This was consistent with Furey and Tilman 46 report, which found that the levels of calcium in grasses and legumes differ noticeably. While P level in this study was above the mean value of 1.2 g/kg DM reported by Muhammad et al 47 , the range of values recorded for Ca in the present study was higher than the 0.7 to 0.9 g/kg DM reported by Muhammad et al 47 .…”
Section: Discussioncontrasting
confidence: 82%
“…This was consistent with Furey and Tilman 46 report, which found that the levels of calcium in grasses and legumes differ noticeably. While P level in this study was above the mean value of 1.2 g/kg DM reported by Muhammad et al 47 , the range of values recorded for Ca in the present study was higher than the 0.7 to 0.9 g/kg DM reported by Muhammad et al 47 .…”
Section: Discussioncontrasting
confidence: 82%
“…Balole and Legwaila (2006) reported that forage sorghum yield annually about 20 Mg green matter ha –1 , which is similar to the DMA recorded at 8 WAP from the present study. The total DMA of irrigated forage sorghum in the Upper East was similar to that reported for forage sorghum when irrigated in the late dry season in the Sudan Savannah of Nigeria (Muhammad et al., 2005).…”
Section: Discussionsupporting
confidence: 81%
“…The values of ADF and NDF reported in this study were lower than 40.0-44.0 % ADF and 61.2-75.3 % NDF in Sorghum almum as reported by Kallah et al (1999). These values were also lower than earlier reports of Muhammad et al (2005) and Olanite et al (2010) except for Negative control. The downward trend observed in the values for fiber fractions (ADF and NDF) among different sources of green manure and inorganic fertilizer (positive control) could be attributed to low Water Soluble Carbohydrate content in grasses, which are characterized by low content of nonstructural carbohydrates that remain in plant parts in the form of soluble sugars and higher nitrogen fertilization diluting the content of the cell wall, this is in accordance with the finding of Neto (2017).…”
Section: Chemical Composition (%) and Fiber Fractions Of Hay Made Fro...contrasting
confidence: 87%
“…The result on Table 6 portrays a linear increase among different sources of green manure in term of percentage CP of hay made from Sorghum almum. The percentage of crude protein when Centrosema pascourum and Lablab purpureum were used as green manure was within the range of 8-10 as reported in a study by Muhammad et al (2005). Higher percentages (%) of CP were recorded when Centrosema pascourum was used as green manure; this could be attributable to higher fixation of atmospheric nitrogen and increase in the synthesis of amino acids and proteins (Oliveira et al, 2010).…”
Section: Chemical Composition (%) and Fiber Fractions Of Hay Made Fro...supporting
confidence: 59%